Family relations, parents’ educational practices, and Angolan adolescents’ values - Laura Galiana; Patricia Sancho; Ana María Santos; Melchor Gutiérrez (Psychology, Society & Education, 2013)
The purpose of this study was three-fold. First, to analyze psychometric properties of the instruments used to evaluate the perceived Family relations, Familiar socialization and Angolan adolescents’ Values. Second, to predict the adolescents’ Values based on Family relations and Family socialization.Third, to analyze adolescents’ Values sex differences. For this aim, 917 adolescents (384 males, 533 females) ages 14 to 17 years (M = 15.68; SD = 1.06)completed Portuguese translations of the Family relations, Family socialization and Value questionnaires. When psychometric properties of the instruments were assessed, a Structural Equation Model (SEM) controlling for sex was carried out, with Family relations and Family socialization as independent variables, and adolescents’ Values as dependent variables. Results showed acceptable psychometric properties of the Portuguese versions of the instruments. Related to the SEM, Familiar functioning predicted Achievement, Universalism, Securityand Conformity; Parents’ Support predicted Benevolence and Conformity; Family difficulties were negatively related with Achievement and Conformity; and Punishment/coercion were negatively related with Achievement, Benevolence and Conformity. The sex variable only differentiated two adolescents’ values. Boys assigned priority to Universalism and girls assigned priority to Conformity. These findings are discussed with regard to the implications to adolescents’ socialization.